Combining chromosome conformation capture and exome sequencing for simultaneous detection of structural and single-nucleotide variants - Maria Gridina; Timofey Lagunov; Polina Belokopytova; Nikita Torgunakov; Miroslav Nuriddinov; Artem Nurislamov; Lyudmila P. Nazarenko; Anna A. Kashevarova; Maria E. Lopatkina; Stanislav Vasilyev; Andrey Zuev; Elena O. Belyaeva; et al. (Genome Medicine)
Abstract Background Effective molecular diagnosis of congenital diseases hinges on comprehensive genomic analysis, traditionally reliant on various methodologies specific to each variant type—whole exome or genome sequencing for single nucleotide variants (SNVs), array CGH for copy-number variants (CNVs), and microscopy for structural variants (SVs). Methods We introduce a novel, integrative approach combining exome sequencing with chromosome conformation capture, termed Exo-C. This method enables the concurrent identification of SNVs in clinically relevant genes and SVs across the genome and allows analysis of heterozygous and mosaic carriers. Enhanced with targeted long-read sequencing, Exo-C evolves into a cost-efficient solution capable of resolving complex SVs at base-pair accuracy. Results Applied to 66 human samples Exo-C achieved 100% recall and 73% precision in detecting chromosomal translocations and SNVs. We further benchmarked its performance for inversions and CNVs and demonstrated its utility in detecting mosaic SVs and resolving diagnostically challenging cases. Conclusions Through several case studies, we demonstrate how Exo-C’s multifaceted application can effectively uncover diverse causative variants and elucidate disease mechanisms in patients with rare disorders.